2015
DOI: 10.1103/physrevb.91.104420
|View full text |Cite
|
Sign up to set email alerts
|

Transverse dynamical magnetic susceptibilities from regular static density functional theory: Evaluation of damping andgshifts of spin excitations

Abstract: The dynamical transverse magnetic Kohn-Sham susceptibility calculated within time-dependent density functional theory shows a fairly linear behavior for a finite energy window. This observation is used to propose a scheme where the computation of this quantity is greatly simplified. Regular simulations based on static density functional theory can be used to extract the dynamical behavior of the magnetic response function. Besides the ability to calculate elegantly damping of magnetic excitations, we derive al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 66 publications
(70 reference statements)
3
66
0
Order By: Relevance
“…It was shown that α int scales with the density of states (DOS) at the Fermi energy n(E F ) in the bcc phase [40], and the DOS also exhibits a sharp minimum for Co 25 Fe 75 . This scaling is expected [63,64] if the damping is dominated by the breathing Fermi surface process. With the breathing surface model, the intraband scattering that leads to damping directly scales with n(E F ).…”
Section: -4mentioning
confidence: 66%
“…It was shown that α int scales with the density of states (DOS) at the Fermi energy n(E F ) in the bcc phase [40], and the DOS also exhibits a sharp minimum for Co 25 Fe 75 . This scaling is expected [63,64] if the damping is dominated by the breathing Fermi surface process. With the breathing surface model, the intraband scattering that leads to damping directly scales with n(E F ).…”
Section: -4mentioning
confidence: 66%
“…Finally, the in-gap states provide a relatively high density of states at the Fermi energy which may profoundly alter the magnetic properties of the system, for instance: the magnetic anisotropy energy [49,50], the response of the impurities to external time-dependent perturbations [51][52][53], their magnetic stability against spin fluctuations [54], and many other phenomena. These properties are currently under investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Ebert et al 1 and Lounis et al 28 suggested that α int is proportional to n(E F ) in the breathing Fermi-surface model (that is, intraband transitions) in the cases of a minimally varying spin-orbit coupling (SOC) (as is the case for the Co x Fe 1−x system) and small electron-phonon coupling 2,29 . Alternatively, interband transitions become significant only if bands have a finite overlap due to band broadening, caused for example by coupling to the phonons.…”
mentioning
confidence: 99%